LC–MS/MS quantification of N-acetylneuraminic acid, N-glycolylneuraminic acid and ketodeoxynonulosonic acid levels in the urine and potential relationship with dietary sialic acid intake and disease in 3- to 5-year-old children. Issue 2 (28th January 2014) - Chen, Yue; Pan, Lili; Liu, Ni; Troy, Frederic A.; Wang, Bing
<x content-type="archive" xml:space="preserve">Abstract</x> Red meat and dairy products contain high sialic acid (Sia) levels, but the metabolic fate and health impact in children remain unknown. The aims of the present study were to quantify the levels of urinary Sia N-acetylneuraminic acid (Neu5Ac), N-glycolylneuraminic acid (Neu5Gc) and ketodeoxynonulosonic acid (KDN) and to determine their relationship with dietary Sia intake. Spot urine samples were collected from 386 healthy children aged 3 (n 108), 4 (n 144) and 5 (n 134) years at 06.30–07.00, 11.30–12.00 and 16.30–17.00 hours. Food intake levels were recorded on the day of urine sample collection. Sia levels were quantified using LC–MS/MS with [13C3]Sia as an internal standard. We found that (1) total urinary Sia levels in healthy pre-school children ranged from 40 to 79 mmol Sia/mol creatinine; (2) urinary Sia levels were independent of age and consisted of conjugated Neu5Ac (approximately 70·8 %), free Neu5Ac (approximately 21·3 %), conjugated KDN (approximately 4·2 %) and free KDN (approximately 3·7 %); Neu5Gc was detected in the urine of only one 4-year-old girl; (3) total urinary Sia levels were highest in the morning and declined over time in 4- and 5-year-old children (P< 0·05), but not in 3-year-old children; (4) Sia intake levels at breakfast and lunch were approximately 2·5 and 0·16 mg Sia/kg body weight; and (5) there was no significant correlation between dietary Sia intake levels and urinary Sia levels. Urinary Sia levels varied with age and time of day, but did not correlate with Sia intake in 3- to 5-year-old children. The difference in urinary Sia levels in children of different age groups suggests that the metabolism and utilisation rates of dietary Sia are age dependent.